Public Service Oversight through Self-Initiated Investigations by the Ombudsman Representative of West Sumatra Province during the 2015-2019 Period - Rezkiarsih, Yosmar; Suherman, Hendra; Ramadhani , Wahyuni (The Future of Education Journal, 2026)
The Ombudsman, as a state institution overseeing public services, implements its supervisory duties by adhering to the active system principle, being proactive in finding evidence, and having the initiative rights, all based on the public interest and the effort to prevent more severe deviations. This principle is stated in Article 7 letter d of Law No. 37 of 2008 concerning the Ombudsman of the Republic of Indonesia (ORI), which mentions that the Ombudsman is tasked with investigating, on its own initiative, allegations of maladministration in public service delivery. Based on this, the research questions formulated are: 1) How is the implementation of public service oversight through self-initiated investigations by the West Sumatra Provincial Representative of ORI? 2) What is the impact of public service improvement through the implementation of public service oversight via self-initiated investigations by the West Sumatra Provincial Representative of ORI? The research approach is juridical-sociological (socio-approach), examining applicable laws and connecting them with on-the-ground facts or the facts related to the formulated problems. Based on the research findings, it can be concluded that the Ombudsman RI West Sumatra Representative has carried out self-initiated investigative duties in accordance with Article 7 letter d of Law No. 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. The number of self-initiated investigations conducted by the West Sumatra Provincial Representative of ORI has varied each year. From 2012 to 2018, 484 self-initiated investigations were conducted, with 31 investigations carried out in 2018. To enhance the accountability of self-initiated investigations and make them more effective and efficient, the Indonesian Ombudsman implemented Regulation No. 38 of 2019 concerning the Procedures for Self-Initiated Investigations. The self-initiated investigations conducted by the Ombudsman RI West Sumatra Representative have led to improvements in public services within the reported institutions. These improvements include service procedure enhancements, system restructuring, and the return of illegal fees.